Pemurnian Minyak Kelapa Sawit Menggunakan Membran Serat Berongga - Nasrul Arahman; Cut Erika; Alfian Putra (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
Characterization of modiﬁ ed polyethersulfone hollow ﬁ ber membranes were carried out in order to purify Palm Oil. Effect of membrane morphology on the separation performances of palm oil was investigated. The modieﬁ ed polyethersulfone hollow ﬁ ber membrane was commercially availbale membrane prepared from the system of polyethersulfone/N-methylpirrolidone/polyvinilpyrrolidone, and polyethersulfone/N-methylpirrolidone/Tetronic 1307. Scanning electron microscopy results show that the modiﬁ ed membranes has macrovoids structure larger than the original poliethersulfone membrane. The hydrophilicity property was also increased by addition of polymeric additive to the membrane system. The maximum ﬂ ux of palm oil reached to 0.47 L/m2.hr. atm obtained from the experimenttal condition as applied pressure of 2.0 kg.cm2, by using membran polyethersulfone/N-methylpirrolidone/polyvinylpirrolidone.ABSTRAKKarakterisasi membran serat berongga (hollow ﬁ ber) dari polimer polietersulfon yang telah dimodiﬁ kasi untuk pemurnian minyak kelapa sawit telah dilakukan. Pengaruh morfologi membran dipelajari terhadap kemampuan pemisahan minyak kelapa sawit. Membran modiﬁ kasi adalah membran komersial yang terbuat dari sistem polyethersulfone/Nmethylpirrolidone/polyvinilpyrrolidone,dan polyethersulfone/N-methylpirrolidone/Tetronic 1307. Hasil karakterisasi dengan SEM menunjukkan bahwa membran yang terbuat dari bahan PES/NMP/PVP, dan PES/NMP/Tetronic 1307 mempunyai struktur macrovoid yang lebih banyak dan ukuran yang lebih besar dibandingkan dengan membran yang terbuat dari bahan PES/NMP. Sifat hidroﬁlisitas membran campuran juga menjadi lebih baik jika dibandingkan dengan membran tunggal PES/NMP. Fluks minyak kelapa sawit terbesar diperoleh 0,27 L/m2.hr.atm pada kondisi tekanan operasi 2,0 kg/cm2 untuk membran hollow ﬁ ber dari bahan PES/NMP/PVP.